“Wavering Conviction”: Interaksi Moral Approbation dan Group Cohesion dalam Konteks Whistleblowing Mahasiswa - Rifki Aprillah Saleh; Tito IM. Rahman Hakim; Prasetyono Prasetyono (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to provide empirical evidence regarding the effect of anger and moral approbation on whistleblowing intention with microsocial ethical environment and group cohesion as moderating variables. Methodology/approach: This paper is an empirical study that delves into behavioral patterns of accounting students from public universities in Madura regarding their intentions to blow the whistle. By using incidental sampling, this study obtains 164 responses. WarpPLS 4.0 is employed to run and test the hypotheses. Findings: From testing four different models, we find that moral approbation and anger significantly promote whistleblowing among students. However, we find no significant relationship for interaction between anger and moral approbation with microsocial ethical environment on whistleblowing intentions. Further, we find the interaction between group cohesion and moral approbation reduces the student’s willingness to report fraud in cases when they have strong self-interest and discretionary grading policy. Practical and Theoretical contribution/Originality: Our findings suggest that public universities in Madura need to take into account the closeness of potential whistleblowers with fraud perpetrators even more in the context of students with low self-interest when developing and implementing whistleblowing systems. These findings suggest the wavering state of students’ convictions of fraud done by their peers. Research Limitation: The results of this study need to be interpreted carefully due to the dominance of small observations in our sample. Our study obtained 164 responses that can be considered sufficient by the analytical tools. However, these numbers are inadequate to generalize our findings, especially when our scope is only three public universities in Madura.